Prevalence and Significance of Non-conventional Antiphospholipid Antibodies in Patients With Clinical APS Criteria - Litvinova, Elena; Darnige, Luc; Kirilovsky, Amos; Burnel, YANN; de Luna, Gonzalo; Dragon-Durey, Marie-Agnes (Frontiers in Immunology, 2018)
Background: The biological diagnostics of antiphospholipid syndrome (APS) takes into account the persistent positivity for anticardiolipin and/or anti-β2GP1 antibodies and/or presence of lupus anticoagulant (LA). However, some non-conventional antiphospholipid antibodies have emerged that could help in the diagnosis of APS. Objectives: To study the potential usefulness of non-conventional antiphospholipid antibodies in clinical practice. Methods: Eighty-seven patients, aged from 15 to 92 years were included and classified in following groups: 41 patients positive for the conventional antibodies with clinical criterion of APS (31 with primary APS and 10 secondary), 17 seronegative APS (SNAPS) patients (i.e., persistent negativity for the conventional antibodies with a strong clinical suspicion of APS), 11 asymptomatic antiphospholipid antibodies carriers (i.e., persistent positivity for the conventional antibodies without clinical evidence of APS), and 18 patients presenting with a first thrombotic or obstetrical event. IgG and IgM were detected to the following antigens: phosphatidylserine/prothrombin (PS/PT) by ELISA, and phosphatidic acid, phosphatidyl-ethanolamine, phosphatidyl-glycerol, phosphatidyl-inositol, phosphatidylserine, annexin V, prothrombin by immunodot. Anti-β2GP1 IgA, and anti-β2GP1 domain 1 IgG were detected by chemiluminescence. Results: Positivity for the non-conventional antibodies was correlated with APS severity; patients with catastrophic APS (CAPS) being positive for 10.7 (Median, Range: 5–14) non-conventional antibodies. 9/17 seronegative patients were positive for at least one of non-conventional antibodies. A study of non-supervised hierarchical clustering of all markers revealed that anti-PS/PT antibodies showed high correlation with the presence of LA. All patients with APS triple positivity (highest risk profile) exhibited also persistent positivity for anti-PS/PT antibodies. Conclusions: Our data obtained from a prospective cohort constituted mainly by patients with primary APS, suggest that non-conventional APS antibodies may be useful for patients classified as SNAPS. They demonstrate the potential value of aPS/PT antibodies as a strong marker of APS. We propose that anti-PS/PT antibodies could be a surrogate APS biological marker of LA to classify in high-risk profile patients treated by direct oral anticoagulants (DOACs), in whom LA detection cannot be achieved.